Civic Education as a Development of Character Education for Elementary School Students - Ni Putu Adi Utami; Dewa Bagus Sanjaya (Indonesian Journal of Instruction, 2025)
Civic Education (PKn) at the elementary school level holds a strategic role in instilling essential character values from an early age. This study aims to explore the role of Civic Education in shaping students' character through the integration of values such as discipline, responsibility, patriotism, and social awareness. Employing a qualitative approach with a case study method, data were collected through classroom observations, in-depth interviews, and document analysis of the PKn learning process. Data were analyzed using descriptive qualitative techniques, including data reduction, data display, and conclusion drawing. The findings reveal that PKn learning, when linked to contextual activities such as classroom discussions, social projects, and extracurricular engagements, significantly enhances students' understanding of citizenship concepts and encourages prosocial behavior. However, limited instructional time, insufficient teacher training in character education, and lack of supporting resources pose major challenges to effective implementation. The study concludes that the effectiveness of Civic Education in character development largely depends on holistic learning approaches and systemic support from curriculum design and professional teacher development. The implications of these findings highlight the urgency of revising the Civic Education curriculum and implementing continuous teacher training programs to fully realize the potential of character education within this subject.